The effect of organizational climate on improving the quality of higher education at the University of Benghazi (Case study of Medical Colleges) (Journal of Pure & Applied Sciences, 2026)
This study aims to identify the effect of organizational climate, including its multiple dimensions considered on improving the quality of higher education at Benghazi University, with special references to its medical colleges. It utilizes the descriptive analytical approach, based on the quantitative method and using the questionnaire- based survey for collecting primary data. The population was (605) academic staffs during conducting the field study. The questionnaire was distributed on a random sample, consisting of (97) participants, with a response rate of (78%). Various statistical methods have been applied for analyzing data, including Cronbach's alpha coefficient, Shapiro-Wilk test, arithmetic means, standard deviation, t-test, and simple and multiple linear regression analysis. Key results show that the organizational climate has a positive, significant impact on improving the quality of higher education. More precisely, they reveal that the dimensions of organizational leadership and structure are the most influential, while the technology did not show a significant impact. However, they indicate that there is a high correlation between the four dimensions of the independent variable. Recommendations have been provided to improving the organizational climate in its multiple dimensions within medical colleges, ensuring the promotion of a positive work environment for faculty members, staff, and students alike, which in turn can positively reflect on raising the level of quality of educational services in these colleges and Benghazi University in general. These recommendations can be useful to all Libyan public universities, given that they are operating in the same external environment and sharing many similar circumstances.